2015
DOI: 10.1007/s00482-015-1513-z
|View full text |Cite
|
Sign up to set email alerts
|

Tötung auf Verlangen und assistierter Suizid

Abstract: The fact that nurses had a more positive attitude towards euthanasia and PAS and that all respondents accepted life-ending acts for themselves more than for their patients hints to still existing severe deficits in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
4
0
4
Order By: Relevance
“…This complies with the results of a study from 2004: only 20% of medical students surveyed in Berlin could imagine a situation in which they would be prepared to kill a patient [12]. Similar results could be seen in a survey by the German Medical Association from 2009; whereas in a study by Zenz et al [18], 32.1% of the doctors surveyed expressed a favorable attitude towards euthanasia. The explicit rejection of euthanasia, as compared to physician-assisted suicide, signals that students – unlike the general population – detect a significant ethical difference between these two treatment approaches, a trend that has also emerged in more recent scientific literature [8].…”
Section: Discussionsupporting
confidence: 88%
“…This complies with the results of a study from 2004: only 20% of medical students surveyed in Berlin could imagine a situation in which they would be prepared to kill a patient [12]. Similar results could be seen in a survey by the German Medical Association from 2009; whereas in a study by Zenz et al [18], 32.1% of the doctors surveyed expressed a favorable attitude towards euthanasia. The explicit rejection of euthanasia, as compared to physician-assisted suicide, signals that students – unlike the general population – detect a significant ethical difference between these two treatment approaches, a trend that has also emerged in more recent scientific literature [8].…”
Section: Discussionsupporting
confidence: 88%
“…The differences in the attitudes of physicians and nurses are remarkable: Physicians are more willing to take action than nurses both in case of a terminal and a non-terminal illness. This result is surprising since former studies prompted to nurses being supportive of euthanasia and PAS [ 26 , 29 , 41 , 42 , 47 ]. However, a study among critical care nurses from Israel also found nurses to be supportive of PAS but only few agreed to participate in this act [ 48 ].…”
Section: Discussionmentioning
confidence: 95%
“…This particular group of professionals is also of special interest in the debate since some have declared euthanasia and PAS as possible outcomes of palliative care [ 22 – 24 ]. In the year before a study was performed at the same conference [ 25 , 26 ]. However, that study focused on support of the legalization of euthanasia or PAS rather than exploring whether the respondents would actually be willing to perform the act.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Umfrage zur Einstellung von Ärzten und Pflegekräften in Deutschland (N = 317) ergab, dass die Zustimmung für PAD im Zusammenhang mit einer nicht tödlichen Erkrankung bei 21,5 % lag. Je höher die Qualifikation (Arzt) und Zusatzweiterbildung (Bereich Palliativmedizin) umso mehr nahm die negative Haltung zu [40]. In einer Datenbankrecherche zu Publikationen über PAD (N = 42) für Personen mit psychischen Störungen wurde festgestellt, dass die meisten Veröffentlichungen zugunsten von PAD von Nichtklinikern (75 %) und gegen PAD von Klinikern (73 %) geschrieben wur- den.…”
Section: Einstellungen Von äRzten Und Psychologenunclassified